2010
DOI: 10.1136/bjo.2010.183301
|View full text |Cite
|
Sign up to set email alerts
|

Balloon catheter dilatation versus probing as primary treatment for congenital dacryostenosis

Abstract: Children who had balloon catheter dilatation had a slightly better success rate than those who had probing; however, this difference was statistically significant only for patients who had a relatively narrow nasolacrimal bone duct.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 25 publications
1
4
0
1
Order By: Relevance
“…Both procedures had a high success rate (86% for probing and 90% for balloon catheter dilatation), that were not diminished in children older than 36 months. Similarly, Goldich et al did not find a significant difference in the surgical outcomes of probing as compared to balloon catheter dilatation, except for patients who had a relatively narrow nasolacrimal bone duct [22]. In general, we agree with the approach that age is not a determinant factor in the decision whether to perform balloon dilatation and silicone intubation in the primary surgery for NLDO.…”
Section: Discussionsupporting
confidence: 80%
“…Both procedures had a high success rate (86% for probing and 90% for balloon catheter dilatation), that were not diminished in children older than 36 months. Similarly, Goldich et al did not find a significant difference in the surgical outcomes of probing as compared to balloon catheter dilatation, except for patients who had a relatively narrow nasolacrimal bone duct [22]. In general, we agree with the approach that age is not a determinant factor in the decision whether to perform balloon dilatation and silicone intubation in the primary surgery for NLDO.…”
Section: Discussionsupporting
confidence: 80%
“…Another confounding factor in this study was that the mean age was 56 months in the balloon catheter group and 18 months in the probing group. 18…”
Section: Discussionmentioning
confidence: 99%
“…11,12 It was originally described as a secondary treatment after failed probing, but recent studies reported high success rates as both a primary and secondary procedure. 1319…”
mentioning
confidence: 99%
“…3 mm aufgepumpt werden kann. Der Behandlung werden Erfolgsraten von 77 bis 90 % zugeschrieben [33,34].…”
Section: Stufe 4 -Dakryoendoskopie Oder Ballonkatheterdakryoplastikunclassified